A Deep Seamount Effect Enhanced the Vertical Connectivity of the Planktonic Community Across 1, 000 m Above Summit. Issue 3 (4th March 2023) - Zhao, Rongjie; Zhao, Feng; Feng, Ling; Fang, James Kar‐Hei; Liu, Chuanyu; Xu, Kuidong
Abstract: Seamount effects, which are generally defined as hydrographic disturbances caused by topography and nutrient enrichment and biological aggregations around seamounts, are normally observed in shallow seamounts due to limited sampling efforts in deep seamounts. However, it remains unclear how and to what extent do deep seamounts leave their imprint on planktonic communities. Herein ciliates, a representative protist group, were chosen to explore the effect of deep seamount on planktonic community. By investigating the vertical and horizontal distribution of ciliate communities around the Kocebu Guyot (summit at −1, 198 m) and in nonseamount area, we revealed an obvious deep seamount effect, which enhanced the vertical mixing of ciliate communities to an extent of over 1, 000 m above the summit. The vertical mixing was manifested by a strong uplift of bottom dwellers from waters deeper than 500 m and a weak uplift from the 300 m layer to the deep chlorophyll maximum (about 150 m) layer. Network analysis showed that the ciliate cooccurrence relationship around the seamount was much more complex than that in nonseamount area. Statistical analysis indicated that seamount significantly weakened the limitation that water depth posed on vertical ciliate distribution. Overall, the ciliate communities presented a much higher‐resolution record of deep seamount effects than physico‐chemical data. Deep seamount could enhance the vertical mixing of waters and cooccurrence complexity of planktonic community to the euphotic layer. Considering the wide existence of deep seamounts, such an effect may have ecological significance and enhance the cycles of matter and energy of global oceans. Plain Language Summary: Seamounts are widely distributed undersea mountains. The specific topography and hydrography of seamounts directly or indirectly enrich the concentrations of particle organic matter and subsequently enhance primary production. This phenomenon is known as a seamount effect and is generally found in shallow (summit depth <200 m) and intermediate seamounts (summit depth 200–400 m). In order to find out whether and to what extent can deep seamount (summit depth >400 m) have a seamount effect on surrounding environments, we explored planktons around a deep seamount with a summit depth of about 1, 200 m. We found a distinct deep seamount effect, which could enhance vertical mixing of planktons to an extent of over 1, 000 m above the summit. The vertical mixing was composed of a strong uplift of benthos in waters deeper than 500 m and a weak uplift from the 300 m layer to deep chlorophyll maximum (about 150 m) layer. Such a deep seamount effect has never been documented before and may have ecological significance and enhance the cycles of matter and energy of global oceans. Key Points: A deep seamount effect upon microplankton was revealed Deep seamount enhanced vertical connectivity and cooccurrence complexity of ciliate community Ciliate communities presented a much higher‐resolution record of deep seamount effects than physico‐chemical data